INVESTIGATING THE LEARNING NEEDS OF THE MOTHERS REGARDING POST OPERATIVE SURGERY HEART CARE OF THEIR INFANTS IN THE HEALTH CENTERS IN TEHRAN - M. Kheradmand; N. Salmanyazdi; M. Alkhani; H. Haghani (Iran University of Medical Sciences, 2005)
Normal transition to a parenthood stage would be critically superimposed by birth of an infant with Congenital Heart Disease (CHD). Providing some information about how to take care of the baby with CHD and heart surgeries and also supporting the mother will decrease maternal stress and consequently improves infant's health. Objective: to investigate the learning needs of the mothers of infants with heart surgeries regarding post operative care in the health centers in Tehran, 1384. Method: the design was a descriptive study in which a questionnaire was as a data gathering instrument. Sixty-two mothers of the infants with congenital heart diseases with continuous sampling method participanted in this study. The study findings showed that 14.5%, 66.1% and 19.4% of mothers had low, moderate and high levels of learning needs respectively. There were not any significant relationships between learning needs and any other variables age or educational levels.  According to the results of the study, providing information to meet the learning needs of mothers would eventually, decrease mother their stress to look after the babies in a better way. Soit seems that, providing educational classes based on the mothers' learning needs would be necessary in the setting of childrens' hospitals with heart surgeries wards. It is recommended that, needs assessment of the mothers of infants with heart surgeries, after discharge, would be necessary for future studies.